2006
DOI: 10.1002/chin.200618227
|View full text |Cite
|
Sign up to set email alerts
|

Termolecular One‐Pot Synthesis of Symmetrical Azines of 4‐Acetyl‐3‐arylsydnones. Hydrazone and Azine Derivatives of 4‐Acetyl‐3‐arylsydnones, Their Spectral Characterization and Biological Properties.

Abstract: Reaction of the corresponding 4-acetyl-sydnones with excess hydrazine leads to the hydrazones (I), whereas a 2:1 ratio yields the azines (II). Both product types are screened for their antimicrobial activities. Compounds with halogen substitution on the phenyl ring [cf. (Ic)-(Ie)] exhibit antibacterial effects, whereas methyl group substitution [cf. (Ib)] increases the activity against fungi. (IId) and (IIe) show enhanced antibacterial activity compared to norfloxacin. -(SHINGE, P. S.; MALLUR, S. G.; BADAMI*, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In 2005, Shinge et al reported the reaction of 4-acetyl-3-arylsydnone derivatives [11] with hydrazine leading to the formation of hydrazones 1 and dimers 2 in good yields and the evaluation of their antimicrobial activities against various Gram-negative bacteria and fungi (Table 1). Determination of the antifungal activity of derivatives 2 led to similar results that their parent monomers 1 (Table 1, derivatives 1e-1f and 2e-2f) whereas weaker activities were encountered against bacteria.…”
Section: ) R Is a Hydrogenmentioning
confidence: 99%
“…In 2005, Shinge et al reported the reaction of 4-acetyl-3-arylsydnone derivatives [11] with hydrazine leading to the formation of hydrazones 1 and dimers 2 in good yields and the evaluation of their antimicrobial activities against various Gram-negative bacteria and fungi (Table 1). Determination of the antifungal activity of derivatives 2 led to similar results that their parent monomers 1 (Table 1, derivatives 1e-1f and 2e-2f) whereas weaker activities were encountered against bacteria.…”
Section: ) R Is a Hydrogenmentioning
confidence: 99%
“…48 Procedure for the Synthesis of 4-Acetyl-3-arylsydnones (2a−d). 49 To a suspension of 5.20 g (0.0369 mol) of phosphorous pentoxide in dry xylene (20 mL) was added 2.00 g (0.0123 mol) of 3-arylsydnones 1a−d in a two-necked RB flask equipped with a reflux condenser with a calcium chloride drying tube. The stirred mixture was heated to reflux on a water bath.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Procedure for the Synthesis of 1-(3-Arylsydnon-4yl)ethylidene)-2-phenylhydrazines (4a−l). 49 4-Acetyl-3arylsydnones 2a−d (1.0 g, 0.005 mol) were dissolved in ethanol (10 mL), and about 3−4 drops of acetic acid were added. Aryl hydrazines 3a−c (0.50 mL, 0.0049 mol) were then added, and the reaction mixture was refluxed for 2 h. The progress of the reaction was monitored by TLC, and after completion of the reaction, the separated solid was filtered, dried, and recrystallized from ethanol to obtain the compounds 4a−l.…”
Section: ■ Conclusionmentioning
confidence: 99%